Prevalence and predictors of malaria-associated acute kidney injury among adults with severe malaria in Tanzania - Punatar, Priyank; Msilanga, Daniel; Mngumi, Jonathan; Shoo, Jacqueline; Msangi, Elizabeth; Nkwera, Upendo; Valentine, Gudile; Batanyita, Julieth; Ruggajo, Paschal (African Journal of Nephrology, 2025)
Introduction: Severe Plasmodium falciparum malaria is a major public health challenge in sub-Saharan Africa, particularly in endemic regions like Tanzania. Among its complications, acute kidney injury (AKI) is one of the most severe, contributing to prolonged hospital stays, poor outcomes, and high mortality especially where dialysis services are limited. Despite its clinical importance, malaria-associated AKI (MAKI) remains under-recognised, and data on its predictors, recovery patterns and long-term kidney outcomes are limited. We report the prevalence, predictors and outcomes of AKI among patients with severe falciparum malaria admitted to Muhimbili National Hospital in Dar es Salaam, Tanzania. Methods: A hospital-based prospective cohort study was conducted in the nephrology wards of Muhimbili National Hospital. Patients with severe Plasmodium falciparum malaria admitted between January and October 2020 were consecutively enrolled. AKI was assessed at admission, after 48 hours, and on day 7. Kidney function was re-evaluated at three months to determine long-term kidney recovery. Associated factors were analysed using chi-squared tests followed by multivariate logistic regression, with a P value of <0.05 considered statistically significant. Results: A total of 318 falciparum malaria patients with a mean age of 40.2 ± 5.1 years were recruited into our study. The prevalence of AKI among severe falciparum malaria patients was 36%. On multivariate logistic regression, we found that advanced age, high parasitaemia count, anaemia and proteinuria were significantly associated with AKI. In-hospital mortality rate for patients with MAKI was 3.5%, and upon 3-monthly follow up, 6.1% of patients with MAKI persisted to chronic kidney disease (CKD). Conclusion: Advanced age, high parasitaemia, anaemia, and proteinuria were independent predictors of developing acute kidney injury (AKI) among our patients with severe Plasmodium falciparum malaria. In addition, malariaassociated AKI was linked to in-hospital mortality and a risk of persistent kidney injury evolving into chronic kidney disease (CKD) at three months, underscoring the importance of early detection and intervention to improve patient outcomes.